Influence of Implant Design on the Biomechanical Environment of Immediately Placed Implants: Computed Tomography-Based Nonlinear Three-Dimensional Finite Element Analysis - Pessoa, Roberto S. [UNESP]; Coelho, Paulo G.; Muraru, Luiza; Marcantonio, Elcio [UNESP]; Vaz, Luis Geraldo [UNESP]; Sloten, Jos Vander; Jaecques, Siegfried V. N. (Quintessence Publishing Co Inc, 2011)
Purpose: To evaluate the influence of different implant designs on the biomechanical environment of immediately placed implants. Materials and Methods: Computed tomography (CT)-based finite element models comprising a maxillary central incisor socket and four commercially available internal-connection implants (SIN SW, 3i Certain, Nobel Replace, and ITI Standard) of comparable diameters and lengths were constructed. Biomechanical scenarios of immediate placement, immediate loading, and delayed loading protocols were simulated. Analysis of variance at the 95% confidence level was used to evaluate peak equivalent strain (EQV strain) in bone and bone-to-implant relative displacement. Results: Loading magnitude (77.6%) and the clinical situation (15.0%) (ie, presence or absence of an extraction socket defect, condition of the bone-to-implant interface) presented the highest relative contributions to the results. Implant design contributed significantly to strains and displacements in the immediate placement protocol. Whereas a greater contribution of implant design was observed for strain values and distributions for immediately placed and immediately loaded protocols, a smaller contribution was observed in the delayed loading scenario. Conclusion: Implant design contributes significantly to changing biomechanical scenarios for immediately placed implants. The results also suggest that avoiding implant overloading and ensuring high primary implant stability are critical in encouraging the load-bearing capability of immediately placed implants. Int J Oral Maxillofac Implants 2011;26:1279-1287
Keywords: dental implant design; finite element analysis; immediate implant loading; immediate implant placement